Visayan Lifescape - Garcia Jr., Moises (Kasarinlan: Philippine Journal of Third World Studies; Vol 15 No 1 (2000): Economies in Flux, 2009)
A book review of Iwao Ushijima and Cynthia Neri Zayas's "Bisayan Knowledge, Movement and Identity."